2014
DOI: 10.3390/sym6040997
|View full text |Cite
|
Sign up to set email alerts
|

MLDS: Multi-Layer Defense System for Preventing Advanced Persistent Threats

Abstract: Abstract:Here we report on the issue of Advanced Persistent Threats (APT), which use malware for the purpose of leaking the data of large corporations and government agencies. APT attacks target systems continuously by utilizing intelligent and complex technologies. To overthrow the elaborate security network of target systems, it conducts an attack after undergoing a pre-reconnaissance phase. An APT attack causes financial loss, information leakage, etc. They can easily bypass the antivirus system of a target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…What's more, we find that it is almost impossible to completely defend against attackers that enter the network through network penetration. [18] However, when an APT invades the system, it will quickly establish a backdoor in the system, so it is inevitable for the APT to try to communicate with the command and control server (C&C server). C&C communication is a bridge between C&C server and the infected user inside the system.…”
Section: B Observation 1) Observation1mentioning
confidence: 99%
“…What's more, we find that it is almost impossible to completely defend against attackers that enter the network through network penetration. [18] However, when an APT invades the system, it will quickly establish a backdoor in the system, so it is inevitable for the APT to try to communicate with the command and control server (C&C server). C&C communication is a bridge between C&C server and the infected user inside the system.…”
Section: B Observation 1) Observation1mentioning
confidence: 99%
“…The Audit expert system is currently widely used [21]. In support of Audit expert systems, Moon et al [22] presented Multi-Layer Defense System (MLDS) that applies a reinforced defense system by collecting and analyzing log information and various information from network infrastructure. Heo et al [23] suggested a system design that helps to maintain a certain level of quality of service and quality of security service in threatening environments.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Matsuda et al, (2018) proposed a new method based on outlier detection and machine learning for detecting attacks that utilize legitimate accounts. A Multi-Layer Defense System which attempts to prevent APTs by analyzing information of network, servers, end-users, and logs, has been proposed by (Moon et al, 2014). Meanwhile, a random forest algorithm has been proposed as a method to detect the presence of APT in infected machines (Chandran et al, 2015).…”
Section: Research On Apt Countermeasuresmentioning
confidence: 99%